In Quest of Spirit: Thoughts on Music - Harvey, Jonathan 1939-2012 (Berkeley University of California Press, 1999)
The interests of the British composer Jonathan Harvey are wide and varied, embracing Christianity, Buddhism, eastern and western philosophy, aesthetics, science, and mysticism. All affect his musical thinking and are a part of this unusual and personal book, which is accompanied by a compact disc featuring works discussed by the author.Harvey explores aspects of music that he connects with spirituality: self-identity, ambiguity, unity, stasis, and silence. In the course of his explorations he offers corroborating statements about music and spirituality from sources ranging from Nietzsche to Oliver Sacks. The book and CD include samples of his own music as well as compositions by Mozart, Scriabin, Stockhausen, and others that help to illustrate the profoundness of what Harvey deems "the good listening experience."For Harvey, composing is his way of trying to live a life "skillfully" in the Buddhist sense. In Quest of Spirit is a window into his creative world and provides a sense of what music can mean at the moment of its inception.
Keywords: Composing